To answer this question, we need to identify the formula for the line equation in the graph.
We can see that if we take two points from the graph, we have:
(0, 0)
(1, 1)
Then, to find the equation for this line, we need to find the slope of the line first:
(0, 0) ---> x1 = 0, y1 = 0
(1, 1) ---> x2 = 1, y2 = 1
The slope is:
![m=(y_2-y_1)/(x_2-x_1)=(1-0)/(1-0)\Rightarrow m=1](https://img.qammunity.org/2023/formulas/mathematics/college/iy212701qdwz0x23pu46wilr5nhefn9xs2.png)
Applying the point-slope form of the line, we have:
![y-y_1=m(x-x_1)\Rightarrow y-0=1(x-0)\Rightarrow y=x](https://img.qammunity.org/2023/formulas/mathematics/college/z5jkkfb5bn0p74q2t9ndi9vwvkcpzoovjq.png)
Then, the function is y = x (as we can check from the graph).
Then, we have that:
![h(x)=-f(x)+3](https://img.qammunity.org/2023/formulas/mathematics/college/ylka6gdzaipa0rsxaobumnj9x4bhu0lyro.png)
And
![f(x)=x\Rightarrow-f(x)=-x](https://img.qammunity.org/2023/formulas/mathematics/college/ftygahhj86i7vx38g9b5c8uyyzfcejjcek.png)
Therefore
![h(x)=-x+3](https://img.qammunity.org/2023/formulas/mathematics/college/gx3oogwz1r0ifmhcxa1dmz3q3fmw41sh0i.png)
Thus, we need to graph this line using the previous equation. We need to find the x-intercept for the line (the value of x when y = 0), and the y-intercept for the line (the value of y when x = 0). Then, we have:
![y=-x+3,y=0\Rightarrow0=-x+3\Rightarrow x=3](https://img.qammunity.org/2023/formulas/mathematics/college/mdhek2w0go4qzn0v2tech7r572h9yw1jne.png)
Then, the x-intercept is (3, 0).
And the y-intercept is (x = 0):
![y=-(0)+3\Rightarrow y=3](https://img.qammunity.org/2023/formulas/mathematics/college/45ihpnb1x9mw7euq3qmn2bbnxjfj96ntks.png)
Hence, the y-intercept is (0, 3).
Therefore, if we put these two points on a graph (3, 0) and (0, 3), the graph will be:
We can see that the line has a different slope, and we can see that the y-intercept is 3, which corresponds with the new function.